Beyond conversation : collaboration and the production of writing - Duffy, William, 1981- (Utah State University Press, an imprint of University Press of Colorado, 2020)
"Outlines an interactionist theory of collaboration to explain collaboration as the rhetorical capacity manifested in discursive engagements coauthors enter into with their writing objects. Interrogates institutional politics around debates about collaboration, offers a history of collaborative writing theory, and proposes a new way of understanding the labor of coauthorship" --